Leadership gold : lessons learned from a lifetime of leading - Maxwell, John C., 1947- (Nashville : Thomas Nelson, 2008)
"Learning to lead effectively"--Provided by publisher.
Searching for Gold vii -- 1 If It's Lonely at the Top, You're Not Doing Something Right 1 -- 2 The Toughest Person to Lead Is Always Yourself 11 -- 3 Defining Moments Define Your Leadership 20 -- 4 When You Get Kicked in the Rear, You Know You're out in Front 32 -- 5 Never Work a Day in Your Life 41 -- 6 The Best Leaders Are Listeners 49 -- 7 Get in the Zone and Stay There 57 -- 8 A Leader's First Responsibility Is to Define Reality 66 -- 9 To See How the Leader Is Doing, Look at the People 74 -- 10 Don't Send Your Ducks to Eagle School 85 -- 11 Keep Your Mind on the Main Thing 96 -- 12 Your Biggest Mistake Is Not Asking What Mistake You're Making 105 -- 13 Don't Manage Your Time-Manage Your Life 114 -- 14 Keep Learning to Keep Leading 124 -- 15 Leaders Distinguish Themselves During Tough Times 134 -- 16 People Quit People, Not Companies 143 -- 17 Experience Is Not the Best Teacher 154 -- 18 The Secret to a Good Meeting Is the Meeting Before the Meeting 164 -- 19 Be a Connector, Not Just a Climber 174 -- 20 The Choices You Make, Make You 184 -- 21 Influence Should Be Loaned but Never Given 193 -- 22 For Everything You Gain, You Give Up Something 203 -- 23 Those Who Start the Journey with You Seldom Finish with You 213 -- 24 Few Leaders Are Successful Unless a Lot of People Want Them to Be 223 -- 25 You Only Get Answers to the Questions You Ask 232 -- 26 People Will Summarize Your Life in One Sentence-Pick It Now 244.
Includes bibliographical references (pages 255-256).
Keywords: Leadership; Industrial management